"Let Me Get You a Nicotine Patch": Nurses' Perceptions of Implementing Smoking Cessation Guidelines for Hospitalized Veterans. Issue 4 (1st April 2016) - Katz, David A.; Stewart, Kenda; Paez, Monica; Holman, John; Adams, Susan L.; Vander Weg, Mark W.; Battaglia, Catherine T.; Joseph, Anne M.; Titler, Marita G.; Ono, Sarah
ABSTRACT: Many hospitalized smokers do not receive guideline-recommended tobacco treatment, but little is known about the perceptions of inpatient nurses with regard to tobacco treatment. We used a sequential explanatory mixed methods design to help explain the findings of an academic detailing intervention trial on the inpatient medicine units of four Veterans Affairs (VA) hospitals. We surveyed 164 nurses and conducted semistructured interviews in a purposeful sample of 33 nurses with different attitudes toward cessation counseling. Content analysis was used to inductively characterize the issues raised by participants. Emerging themes were categorized using the knowledge-attitudes-behavior framework of guideline adherence. Knowledge-related and attitudinal barriers included perceived lack of skills in cessation counseling and skepticism about the effectiveness of cessation guidelines in hospitalized veterans. Nurses also reported multiple behavioral and organizational barriers to guideline adherence: resistance from patients, insufficient time and resources, the presence of smoking areas on VA premises, and lack of coordination with primary care. VA hospitals should train inpatient staff how to negotiate behavior change, integrate cessation counseling into nurses' workflow, develop alternative referral mechanisms for post-discharge cessation counseling, and adopt hospital policies to promote inpatient abstinence.